2023
DOI: 10.1186/s12889-023-15013-2
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling concepts of inappropriate polypharmacy in old age: a scoping review

Abstract: Introduction Polypharmacy is a common concern, especially in the older population. In some countries more that 50% of all individuals over 60 receive five or more drugs, most often due to multimorbidity and increased longevity. However, polypharmacy is associated with multiple adverse events, and more medication may not always be the answer. The terms “appropriate” and “inappropriate” are often used to distinguish between “much” and “too much” medications in relation to polypharmacy in research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…11 Polypharmacy may, however, be appropriate to treat multiple long-term conditions and hence there is ever increasing attention paid to the concept of 'inappropriate' polypharmacy, whereby medicines are prescribed in excess of therapeutic need, or in ways that are harmful. 14 There are a number of medicine classes that are known to increase the risk of adverse drug events in older people, including hypnotics, antipsychotics, hypoglycaemics and anticoagulants, 15 which all featured in our current study. Hypnotics are associated with increased risk of confusion, muscle weakness, and falls, which impact older people to a greater extent than younger people, and in our study, these were prescribed at similar rates as those seen in the general 75+ years population in NZ.…”
Section: What Gap This Fillsmentioning
confidence: 88%
“…11 Polypharmacy may, however, be appropriate to treat multiple long-term conditions and hence there is ever increasing attention paid to the concept of 'inappropriate' polypharmacy, whereby medicines are prescribed in excess of therapeutic need, or in ways that are harmful. 14 There are a number of medicine classes that are known to increase the risk of adverse drug events in older people, including hypnotics, antipsychotics, hypoglycaemics and anticoagulants, 15 which all featured in our current study. Hypnotics are associated with increased risk of confusion, muscle weakness, and falls, which impact older people to a greater extent than younger people, and in our study, these were prescribed at similar rates as those seen in the general 75+ years population in NZ.…”
Section: What Gap This Fillsmentioning
confidence: 88%
“…The analgesic ladder, vertebroplasty, and complementary and alternative medicine were also effective in controlling pain [ 35 ]. However, the study showed that the polypharmacy increased mortality, falls, adverse drug reaction, and hospitalization and readmissions [ 38 ]. Decreasing the drug use of the patients are not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate polypharmacy and its associated adverse outcomes have prompted researchers to explore factors contributing to this phenomenon (Lau et al, 2023). Studies have identi ed several determinants of polypharmacy, including the presence of multiple chronic conditions, depressive symptoms, and prescribing practices (Chuang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%